Demand, Competition, and Public Policy in the Automobile Industry - Johannes Van Biesebroeck; Frank Verboven (Journal of Economic Literature, 2026)
We review the flourishing literature on the automobile industry since the seminal work of Berry, Levinsohn, and Pakes (1995), or briefly BLP. Their work provides a structural equilibrium framework that forms a basis for conducting policy counterfactuals in several key areas of interest: competition policy and antitrust, trade policy, and taxation and environmental policy. The demand side of the “BLP framework” is micro-founded and allows for rich consumer heterogeneity to generate flexible substitution patterns between products. The supply side specifies marginal costs and accounts for imperfect competition. Our analysis focuses on two main questions. First, how has the framework been tailored to specific situations and how convincingly has it been evaluated to generate trust in the empirical findings and policy conclusions? Second, what has been learned about policy issues relevant in the automotive industry using the BLP equilibrium framework? (JEL H25, K21, L13, L22, L40, L62, Q58)